Katrina Kosec, "POLICY SEMINAR Information, Governance, and Rural Service Delivery Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM)" - Kosec, Katrina (2019)
Katrina Kosec POLICY SEMINAR Information, Governance, and Rural Service Delivery Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM)